The publishing history of Uncle Tom's cabin, 1852-2002 - Parfait, Claire (Ashgate, 2007)
Until now, no book-length study has traced the tumultuous publishing history of Uncle Tom's Cabin, the most famous of antislavery novels. Claire Parfait follows the trail over 150 years, along the way addressing the conditions of female authorship, the structures of copyright, author-publisher relations, agency, and literary economics. Scholars of Stowe, of American literature and culture, and of publishing history will find this impressive and compelling work invaluable.